2010
DOI: 10.1293/tox.23.31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Short-term Myelotoxicity Study in Dietary Reduced Rats

Abstract: This study attempted to prove our hypothesis that a short-term toxicity study, using a 4-day dosing regimen as an example, is suitable for evaluating myelotoxicity in rats. We compared the hematological, bone marrow cytological and histopathological results of 5-fluorouracil (5-FU) treated and pair-feeding groups after a 4-day administration period. Several experimental groups were defined for this 4-day study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…However, decreases in peripheral blood reticulocytes and bone marrow erythroids, increases in the marrow M/E ratio and SI level, and a decrease in the UIBC were observed as changes that suppressed erythropoiesis in the R33 and R66 groups and as changes that were reflected by the decrease in body weight gain. These erythropoietic changes agreed with the result of our previous studies [1,2,22] in that they sensitively reflected the influence of undernutrition. The marrow M/E ratio increased because of a decrease in the marrow erythroid counts.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, decreases in peripheral blood reticulocytes and bone marrow erythroids, increases in the marrow M/E ratio and SI level, and a decrease in the UIBC were observed as changes that suppressed erythropoiesis in the R33 and R66 groups and as changes that were reflected by the decrease in body weight gain. These erythropoietic changes agreed with the result of our previous studies [1,2,22] in that they sensitively reflected the influence of undernutrition. The marrow M/E ratio increased because of a decrease in the marrow erythroid counts.…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported that increases in reticulocytes were observed more frequently in the 5-FU administration group (oral gavages, 15 and 18 mg/kg/day for 14 days with a 7-day recovery period) than in the corresponding pair-feeding group at the end of the recovery period, though a severe reduction in reticulocytes was observed in those groups at the end of the administration period [1,22]. These findings were not observed in a pair-feeding group in a 4-day study protocol, since concerns regarding the influence of secondary changes related to undernutrition were minimized for this short-term study protocol [2]. Burkhard et al [5] reported that anemia induced in weanling rats by feeding them an iron-deficient diet resulted in a decrease in reticulocytes with bone marrow erythroid hypoplasia, and an increase in reticulocytes was seen in these rats after a hemolytic event.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is indicative of big vulnerability of haematopoiesis to changes, especially among young animals which bone marrow cells are in constant increased proliferation and differentiation. It can be assumed that adult rats with decreased body weight caused by taking compound or medicine will be more relevant to assess their myelotoxicity [2,3]. Tang et al (2016) have carried out an interesting and innovative research in which consequences of 30% food restriction among adult animals were analysed.…”
Section: The Influence Of Malnutrition and 5-fluorouracil Supply On Hmentioning
confidence: 99%
“…Most researchers analyzing the impact of malnutrition on hematopoiesis focused on changes in the process of erythropoiesis. However, there are also studies on other hemopoietic pathways -granulocytopoiesis, and lymphocytopoiesis [10].…”
mentioning
confidence: 99%